Cognitive Behavioral Therapy Group Counseling to Improve Body Image (Universitas Negeri Semarang, 2018)
This study aimed to examine the effectiveness of cognitive behavioral therapy group counseling to improve the body image of the students of Kesatrian 2 Junior High School (SMP 2 Kesatrian) Semarang. Meanwhile, the research methods used were repeated measures of experimental design with pretest and multiple posttest design. For more, the sample used were 7 students selected by using purposive sampling technique. The results of this study showed that cognitive behavioral therapy group counselling was effective to improve students’ body image. At last, the findings succeeded in proving the effect of cognitive behavioral therapy group counseling towards the body image of junior high school students.